The surfactant co-formulant POEA in the glyphosate-based herbicide RangerPro but not glyphosate alone causes necrosis in Caco-2 and HepG2 human cell lines and ER stress in the ToxTracker assay. (October 2022) - Mesnage, Robin; Ferguson, Scarlett; Brandsma, Inger; Moelijker, Nynke; Zhang, Gaonan; Mazzacuva, Francesca; Caldwell, Anna; Halket, John; Antoniou, Michael N.
Abstract: The toxicity of co-formulants present in glyphosate-based herbicides (GBHs) has been widely discussed leading to the European Union banning the polyoxyethylene tallow amine (POEA). We identified the most commonly used POEA, known as POE-15 tallow amine (POE-15), in the widely used US GBH RangerPro. Cytotoxicity assays using human intestinal epithelial Caco-2 and hepatocyte HepG2 cell lines showed that RangerPro and POE-15 are far more cytotoxic than glyphosate alone. RangerPro and POE-15 but not glyphosate caused cell necrosis in both cell lines, and that glyphosate and RangerPro but not POE-15 caused oxidative stress in HepG2 cells. We further tested these pesticide ingredients in the ToxTracker assay, a system used to evaluate a compound's carcinogenic potential, to assess their capability for inducing DNA damage, oxidative stress and an unfolded protein response (endoplasmic reticulum, ER stress). RangerPro and POE-15 but not glyphosate gave rise to ER stress. We conclude that the toxicity resulting from RangerPro exposure is thus multifactorial involving ER stress caused by POE-15 along with oxidative stress caused by glyphosate. Our observations reinforce the need to test both co-formulants and active ingredients of commercial pesticides to inform the enactment of more appropriate regulation and thus better public and environmental protection. Highlights: The toxicity of co-formulants present in glyphosate-based herbicides has been widely investigated. We identified POE-15 tallow amine in the widely used US herbicide RangerPro. Glyphosate and RangerPro but not POE-15 caused oxidative stress in HepG2 cells. RangerPro and POE-15 tallow amine but not glyphosate gave rise to ER stress. RangerPro toxicity involves ER stress caused by the surfactant and oxidative stress caused by glyphosate.